1975
DOI: 10.1136/gut.16.10.776
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin response to meals of different composition in normal subjects.

Abstract: SUMMARY The serum gastrin responses and the integrated gastrin responses to eating three meals of very different composition were studied in the same normal subjects on different days. Two meals, a milk meal of 500 ml, and a breakfast of eggs, toast, butter, marmalade, fruit juice and coffee, were eaten at breakfast time. The serum gastrin responses to these meals were compared and contrasted with the concentrations observed when the subjects fasted over the same time of day. A steak meal was eaten at lunch ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…The need to standardize the feeding tests used to assess the gastrin response to food ingestion in man has been pointed out by Blair et al (2). Among the sources of variations the composition of the meal and the amount of food 160-o 150g V; 2.6*2.37X r=0.95 p< 0.001…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to standardize the feeding tests used to assess the gastrin response to food ingestion in man has been pointed out by Blair et al (2). Among the sources of variations the composition of the meal and the amount of food 160-o 150g V; 2.6*2.37X r=0.95 p< 0.001…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the composition of the meal and the reproduc ibility of the gastrin response to a standard meal must indeed be established. To our knowledge, only Blair et al (2) compared in the same subjects the plasma gastrin response to meals of different composition and tested the reproducibility of the response.…”
mentioning
confidence: 99%
“…But no clear-cut difference was observed in the gastrin release between the two test meals mentioned above. The need to standardize the releasing test of gastrin has been pointed out by Blair et al (1975). Various kinds of foods such as liquid meal, steak and meat extract were employed in many reports, but the results were not satisfactory.…”
Section: Rate Of Increase In Gastrin Releasementioning
confidence: 99%
“…Therefore, liver extract, meat extract and various kinds of meals are often used for testing gastrin release. In this respect, Blair et al (1975) reported that there were no significant differences in the peak gastrin response after meals varying in composition. In order to standardize the feeding test used to assess the gastrin response, protein feeding tests were employed.…”
mentioning
confidence: 94%
“…glucose BY N. F. KNIGHT*, A. P. MARR, D. J. SANDERS, C. W. VENABLES* and S. ZAHEDI-ASL. Physiology and Surgery* Departments, The Medical School, Newcastle upon Tyne NEJ 7RU We have previously reported to the Society that after eating a standard breakfast (Blair, Greenwell, Grund, Reed & Sanders, 1975), a group of patients with endoscopically proven active duodenal ulcer (DU) had significantly higher plasma insulin, significantly lower plasma glucose concentrations (Knight, Sanders, Venables & Zahedi-Asl, 1980), and higher plasma glucose-dependent insulinotrophic peptide (GIP) and gut glucagon concentrations than control (Knight, Marr, Moody, Sanders, Venables & Zahedi-Asl, 1981). We concluded that the high plasma GIP probably caused the high plasma insulin concentrations which in turn caused the low glucose concentrations in DU patients.…”
Section: Pmentioning
confidence: 99%